Three-Component One-Pot Synthesis of Unsymmetrical Diarylalkynes by Thermocontrolled Sequential Sonogashira Reactions Using Potassium Ethynyltrifluoroborate - Kim, Taejung; Jeong, Kyu Hyuk; Kim, Youngseok; Noh, Taesub; Choi, Jaeyoung; Ham, Jungyeob (WILEY-V C H VERLAG GMBH, 2017)
Unsymmetrical diarylalkynes were synthesized in moderate to good yields through a three-component one-pot procedure involving thermocontrolled sequential Sonogashira reactions with potassium ethynyltrifluoroborate and two different reactive aryl halides. The one-pot procedure was initiated by the palladium/copper-catalyzed Sonogashira coupling of potassium ethynyltrifluoroborate to an aryl iodide or electron-deficient aryl bromide at 40 degrees C. Following a subsequent deboronative Sonogashira reaction of the in situ generated potassium (arylethynyl)trifluoroborate, a second coupling to a less-active electron-rich aryl bromide at 80 degrees C, without any additional palladium/copper catalyst or base, gave rise to unsymmetrical diarylalkynes.
Keywords: ARYL CHLORIDES; PROPIOLIC ACID; COUPLING REACTIONS; CATALYTIC-SYSTEMS; CHARGE-TRANSFER; EFFICIENT; ALKYNES; DIARYLACETYLENES; POLYMERS; ALCOHOLS